HERMEUNEUTICS PARADIGM: AN INSIGHT IN THE APPLICATION OF A MEANINGFUL FUNCTIONAL ENGLISH GRAMMAR - Ferlya Elyza; Rini Susiani (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This article portrays the fundamental paradigm of language, English in this case, which has transformed from a traditional point of view to a functional one. Dealing with the mandate of the curriculum, both of primary education and tertiary education curriculum, that language learning does not rely simply on patterns, pronunciation, and vocabulary. However, language learning is a learning process by involving the effort in enabling students to strengthen four English skills, listening speaking reading and writing. Though, in this era, communicative competence has been the ultimate goal of language teaching orientation (Savignon, 2017). Changing the mindset of language is not just learning the rules, but also how to change with the mindset that learning language is to be able to actualize students and enable them to use language communicatively and contextually. This view is in line with the hermeneutics philosophical view. It sees language learning as being able to understand meaning and interpret meaning based on context and situation. Language teachers are expected to understand those differences through managing teaching learning process in traditional view and functional view.